The Effect of Agency Costs on Hedging Policy in Indonesian Public Companies - Paranita, Ekayana Sangkasari; Aditya, Elma Muncar (Department of Management, Faculty of Economics, Universitas Negeri Semarang, 2020)
The purpose of this study is to examine the effect of agency costs on company hedging policies. This study use the concept of hedging policies derived from synchronizing foreign exchange derivatives based on agency theory and hedging with foreign exchange debt based on balancing theory. The novelty of this research is the application of the synthesis of agency theory and balancing theory as indicators of hedging policies. The hedging policy based on foreign exchange derivatives is synchronized with the hedging policy based on foreign debt. The population was companies listed on the Indonesia Stock Exchange (IDX) in 2012-2017. Using the purposive sampling method, 78 companies for each year from 2012 - 2017 were obtained with a total of 468 data. This research used a panel data regression method. The hypotheses were tested with the Hausman Test, which shows the best research model is the Fixed Effect Model. The results of the study concluded that financial distress and underinvestment had a significant positive effect on hedging policies, while business risk did not affect hedging policies because most companies had relatively low foreign sales. The findings of this study have theoretical implications that support agency and balancing theory.